If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-5(x+1)=-5-2x
We move all terms to the left:
3x-5(x+1)-(-5-2x)=0
We add all the numbers together, and all the variables
3x-5(x+1)-(-2x-5)=0
We multiply parentheses
3x-5x-(-2x-5)-5=0
We get rid of parentheses
3x-5x+2x+5-5=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 7y+20+3y=180 | | 10=j-8 | | (15x+8)°=(21x-10)° | | 7=5+-b | | 0=-16t2+24t+6. | | 9q+6=4q-14 | | 12.8=m-3.8 | | (2x+6)+5x=8x-11 | | (6x-9)=4x+12 | | 28=f+16 | | 56=11x-76x= | | x^2+5x−14=0. | | 14x-5-4x=45 | | 10x-54=5(2x+4) | | 2(1.15x+1.4)=-1.2x+9.8 | | 64=8*g | | -12=6b+12 | | 3(x+1=5(x+3) | | 0.32=0.4e | | w*3=36 | | -x+59=258 | | 10^10−3x=10,000 | | 6x+4+14x+6=130 | | 44+2x=60 | | 60=c*15 | | 126-x=212 | | -7c-6c=20 | | 48=3*a | | -x+231=130 | | 14y+20=-16+11y | | a*18=72 | | -4(8n-6)=-406 |